2019
DOI: 10.1038/s41598-019-53115-3
|View full text |Cite
|
Sign up to set email alerts
|

Accurate whole-night sleep monitoring with dry-contact ear-EEG

Abstract: Sleep is a key phenomenon to both understanding, diagnosing and treatment of many illnesses, as well as for studying health and well being in general. Today, the only widely accepted method for clinically monitoring sleep is the polysomnography (PSG), which is, however, both expensive to perform and influences the sleep. This has led to investigations into light weight electroencephalography (EEG) alternatives. However, there has been a substantial performance gap between proposed alternatives and PSG. Here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
78
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 24 publications
7
78
2
Order By: Relevance
“…A study by Mikkelsen et al investigated the feasibility of sleeping with dry contact ear-EEG in 20 adults in a sleep laboratory. 12 They found that 80 % of the participants reported the ear-EEG as easy to use, which is slightly lower compared to the results of our study where 93.8 % did not nd it challenging to apply the sensors. In addition, Mikkelsen et al found that 20 % rated their sleep quality as bad with the ear-EEG, which is comparable to our study.…”
Section: Feasibilitycontrasting
confidence: 78%
“…A study by Mikkelsen et al investigated the feasibility of sleeping with dry contact ear-EEG in 20 adults in a sleep laboratory. 12 They found that 80 % of the participants reported the ear-EEG as easy to use, which is slightly lower compared to the results of our study where 93.8 % did not nd it challenging to apply the sensors. In addition, Mikkelsen et al found that 20 % rated their sleep quality as bad with the ear-EEG, which is comparable to our study.…”
Section: Feasibilitycontrasting
confidence: 78%
“…Furthermore, the raw data might be dumped from the commercial polysomnogram (PSG) and the raw data might have been filtered at the frequency range 0.3-35 Hz. Due to the advance of technology and focus on large-scale applications, there is an increasing number of mobile devices capable of recording EEG signal in in-home settings (e.g., single channel amplifiers on the forehead or in-ear/around ear applications) [6][7][8][9]. These mobile solutions might not include EMG and EOG information, and the raw data might be bandpassed for different purposes, like data storage or transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Longterm measurements over days or real-life measurements carried out by the test person are thus excluded [1]. Such a constant contact to the person would offer possibilities such as monitoring patients during sleep [2], detecting driver drowsiness [3] or attention focusing of auditory attention [4] for the improvement of hearing aids.…”
Section: Introductionmentioning
confidence: 99%
“…In this approach, several electrodes are realized on an earplug and conduct the electrical cortical signal in the auditory canal and the auricle. Concepts range from flexible silicone plugs with conductive silicones or coatings [8][9][10] to hard shells that are adapted to the respective ears with individually attached electrodes that have been cut out or metal pastes that have been applied manually [2,12]. Especially, porous silver chloride is often used, which degrades over time, and conductive gel [11] must be used for acceptable measurements, which excludes long-term measurements, as this dries out over time.…”
Section: Introductionmentioning
confidence: 99%